IMPORTANCE AND EFFECTIVENESS OF COOPERATION BETWEEN SUFFA INTERNATIONAL RADIO OBSERVATORY AND JIZAKH STATE PEDAGOGICAL INSTITUTE - Hotamov, Jaxongir; Hotamova, Nigora (Физико-технологического образование, 2021)
The importance and effectiveness of the formation of practical skills in teaching students of the direction "Methods of teaching physics and astronomy" of the Jizzakh State pedagogical institute of the International Radio Observatory "Suffa" RT-70.